Acupuncture Treatment of Diabetic Peripheral Neuropathy in an American Indian Community - Anne Bailey; Deborah Wingard; Matthew Allison; Priscilla Summers; Daniel Calac (Medical Association of Pharmacopuncture Institute, 2017)
Diabetic peripheral neuropathy (DPN) develops in 30% of type 2 diabetes patients, increases the risk for foot ulcers and amputation, and is a significant source of disability and medical costs. Treatment remains challenging, propelling research to focus on therapeutic methods that aim to improve blood circulation or ameliorate oxidative stress that drives development of DPN. The aim of this study was to assess the effectiveness of acupuncture treatment for DPN symptoms and lower extremity arterial circulation in people with type 2 diabetes. Twenty-five patients seen at a Southern California Tribal Health Center who reported a threshold level of diabetic neuropathy symptoms in the lower extremities during the previous 4 weeks received acupuncture treatment once per week over a 10-week period between 2011 and 2013. The Neuropathy Total Symptom Scale (NTSS-6), Neuropathy Disability Score (NDS), and laser Doppler fluxmetry (LDF) were used for assessment at baseline and 10 weeks. A total of 19 of 25 study participants completed the study and reported a significant reduction in the NTSS symptoms of aching pain, burning pain, prickling sensation, numbness, and allodynia. Lancinating pain did not decrease significantly. LDF measures improved but not significantly. Acupuncture may effectively ameliorate selected DPN symptoms in these American Indian patients.